Women’s Development at the Margins: Incarcerated Women’s Search for Self - M. Carolyn Clark (Adult Education Research Conference, 2000)
This study examines how one group of marginalized women, the incarcerated, construct their sense of self. Using the notion of nonunitary subjectivity to analyze life history narratives, I demonstrate how multiple positionings within available discourses serve to disadvantage these women.